Improving Learning Outcomes of Class VIII-F Students by Implementing Clipping Assisted Articulation Learning Models at Kediri 3 Public Middle School on Indonesian Language Lessons Reading News Materials - Gianto, Gianto (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
The learning process of Indonesian in Class VIII-F of SMPN 3 Kediri experienced several obstacles. The obstacle is the low interest and activeness in following the learning process. This causes low student learning outcomes that are lacking. This study aims to improve the learning outcomes of students VIII-F SMP 3 Kediri by using the Articulation learning model. Data collection methods used were observation, written tests, and documentation. The application of the articulation learning model starts with the teacher giving the material followed by group formation. After that, the teacher gives news text to each group. One student from each group has the duty to read the text and the other students record important things. After reading the text, the text is taken back by the teacher. Then the teacher gives a list of questions related to the news text Each group must discuss to answer the question. The indicator of the success of this study is that there are more than 75% of students who complete KKM. Based on the research data it can be seen that in pre-cycle there were 47% (16) students completed KKM. Then, in the first cycle, there were 62% (21) students completed KKM. Then, in the second cycle, there were 82% (28) students completed KKM.